Pseudomonas aeruginosa isolates from cystic fibrosis patients induce neutrophil extracellular traps with different morphologies that could correlate with their disease severity - S. Martínez-Alemán; A.E. Bustamante; R.J. Jimenez-Valdes; G.M. González; A. Sánchez-González (Elsevier, 2020)
Cystic fibrosis (CF) is a disease characterized by bacterial chronic infection of the respiratory tract and inflammation, which leads to a progressive decrease in lung function. Pseudomonas aeruginosa is commonly isolated from the sputum of patients and their presence is associated with a predominant airway inflammation with neutrophils, causing chronic colonization and higher mortality rates. Neutrophil extracellular traps (NETs) have been observed in response against Pseudomonas, however, these cannot eliminate the pathogen from the respiratory tract, so one possibility is that the bacteria could promote their production to use them as a scaffold to colonize the lungs and as a nutrient source, however, their overproduction could also lead to increased damage to the lungs. In this work, we evaluated NETs formation by Pseudomonas clinical isolates obtained from CF patients and found that these induced NETs formation with globular or spread morphologies, of note, we found that there is a trend by which the spread forms were induced mainly by isolates obtained from patients with severe disease, whereas, the globular morphologies were observed for isolates obtained from patients with mild/moderate disease. Finally, we screened for bacterial molecules implicated in NETs formation and found that Exotoxin S, pyocin S2 and pyoverdine could participate in the process.